Predictive value of neutrophil to lymphocyte ratio and platelet to lymphocyte ratio in advanced hepatocellular carcinoma patients treated with anti–PD‐1 therapy. (18th May 2020) - Dharmapuri, Sirish; Özbek, Umut; Lin, Jung‐Yi; Sung, Max; Schwartz, Myron; Branch, Andrea D.; Ang, Celina
Abstract: Background: Currently, there are no recognized or validated biomarkers to identify hepatocellular carcinoma patients (HCC) likely to benefit from anti–PD‐1 therapy. We evaluated the relationship between neutrophil‐lymphocyte ratio (NLR) and platelet‐lymphocyte ratio (PLR) and survival outcomes, pretreatment and after three doses (posttreatment) of nivolumab in HCC patients. Methods: Medical records of HCC patients treated with nivolumab between June 2016 and July 2018 were reviewed. Kaplan‐Meier analysis and the log‐rank test were used to calculate and compare overall survival between NLR < 5 Vs ≥ 5 and among PLR tertiles. Results: A total of 103 patients were identified. Median age was 66 (29‐89) years. Median treatment duration was 26 (2‐149) weeks. Sixty‐four (62%) patients had Child‐Pugh class A (CP‐A) liver function. Barcelona Clinic Liver Cancer stage was B in 20 (19%) and C in 83 (81%) patients. CP‐A patients who achieved a partial or complete response had significantly lower posttreatment NLR and PLR ( P < .001 for both) compared to patients who had stable disease or progression of disease. No relationship was observed between response and pretreatment NLR and PLR. NLR < 5 was associated with improved OS compared to NLR ≥ 5 both pretreatment (23 Vs10 months, P = .004) and posttreatment (35 Vs 9 months, P < .0001). Survival also differed significantly among PLR tertiles both pre‐ ( P = .05) and posttreatment ( P = .013). In a multivariable model, posttreatment NLR (HR = 1.10, P < .001) and PLR (HR = 1.002, P < .001) were strongly associated with survival. In a composite model of posttreatment NLR and PLR, a combination of high NLR and PLR was associated with an eightfold increased risk of death (HR = 8.3, P < .001). Conclusions: This study suggests a strong predictive role of these inflammatory cell ratios in the posttreatment setting in HCC patients treated with anti anti–PD‐1 therapy and should be evaluated in a larger cohort. Abstract : In this study evaluating 103 patients with advanced hepatocellular carcinoma, lower neutrophil‐lymphocyte ratio (NLR) and platelet‐lymphocyte ratio (PLR) were both strongly predictive of improved survival after three cycles of nivolumab. Baseline NLR was not associated with survival. An elevated NLR and PLR in the posttreatment setting may be an early sign of treatment failure and may warrant consideration for early change in therapy.